A distribuição física de produtos como recurso competitivo: uma análise na empresa de laticínios - Leão, Bruno Layson Ferreira (Universidade Federal Rural do Semi-Árido, 2017)
In a scenario of globalization, markets become increasingly competitive, requiring business managers to obtain competitive advantages that position them robustly against their competitors. The theoretical perspective of Resource Based View brings a focus to the understanding of organizational resources as sources of competitive advantages through their 8 strategic alignment to the creation of economic value for companies. In this way, the VRIO model, a tool capable of ascertaining which features have characteristics necessary to build strong competitive elements with sustainability in terms of competition, is currently used to evaluate the competitive implications of each strategic resource of companies. Taking into consideration the prominence of the distribution activities of the dairy company studied, this study aimed to analyze if the physical distribution of the analyzed company can generate competitive advantage. For this, the following specific objectives have been developed, be they: To find out how the physical distribution is used in the company; and Investigate the physical distribution of the company from the VRIO Model. The work was done semi-structured interviews with the managers of the distribution unit analyzed by the dairy company, and questionnaires addressed to its retail customers based in the city of Mossoró. The data analysis showed the activity flow of the company's distribution activities and its adjustment of the service level, capable of adding value to the retail customer through the availability of products in a perspective that considers the precision, agility, and minimum margin of errors as core values. It has been realized that the company has five distinct competitive resources, be they: flexibility in the flow of activities, location, ERP system, staff, and reputation. Among these resources, only Reputation is able to claim sustainable competitive advantage for the company, while Location is a source of temporary competitive advantage and the other resources guarantee only competitive parity against the competition. The present study brought contributions to the field of RBV by shedding light on issues related to physical distribution and under what conditions of operation of these activities could be the opportunity to generate competitive advantage, to which it was reached the understanding that a mix of structural resources and relational-interpersonal, aligned, can determine the success of the operations and their competitiveness before the market.
Monografia
Keywords: Distribuição física; RBV; VRIO; Vantagem competitiva; Physical distribuction; RBV; VRIO; Competitive advantage; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO